Preparation and characterization of Si02-Zr02 doped with Er3+ and Er3+/Yb3+ glass ceramic thin film / Nurul Iznie Razaki - Razaki, Nurul Iznie (2013)
In this thesis, the Er3+ and Er3+/Yb3+ doping dependents of 70Si02-30Zr02 glass ceramics thin film are studied. All the samples were prepared via sol-gel dip coating technique and annealed at 900 to 980°C. Full film densification was achieved for the deposited film, which indicates hydroxyl group was successfully removed, as depicted by Raman spectra. Presence of higher rare earth ions raises the refractive index of the films, thus enabling the guiding of light in the film structure. Green and red emissions of Er3+ were observed upon 514.5nm excitation. At higher doping of Er3+ (0.58 mol %), concentration quenching occurs as depicted by a decrement of green emission.Meanwhile, the red emission increases as a function of Er3+-doping. Addition of Yb3+ as co-dopant with Er3+/Yb3+ proportions of 1/3, 1/5 and 1/10 in the highly doped of Er3+ (0.58 mol %) decreases the both emission with the red emission dominates the radiative transition. With further increased of Er3+ in highly doped of Yb3+ (5.8 mol %), there is no significant changes on the emission as the amount of Er3+ reached up to 0.9 mol%. Existence of ZrC>2 tetragonal phase at lower temperature is due to presence of RE doping and rapid thermal annealing of the film. Crystallization of the film gives rise to sharp and narrow peak of Er3+ emission spectrum. Films with Yb3+ ions co-doping demonstrate less crystallinity, as characterized by Raman spectroscopy and X-Ray Diffraction (XRD). XRD study also show that the samples with Yb3+ codoping have small crystallite size, which is consistent with Atomic Force Microscopy (AFM) measurement as the samples demonstrate low surface roughness.